Efektivitas Program Pamsimas di Nagari Padang Air Dingin Kecamatan Sangir Jujuan Kabupaten Solok Selatan - Riza Malia Efni; Waza Karia Akbar; Wibi Wijaya (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The PAMSIMAS program is one of the goals of the Millennium Development Goals (MDGs), namely to improve people's welfare and community development. One of them is in the development of drinking water and sanitation (water supply and sanitation). As a basic public service, based on Law no. 23 of 2014 concerning Regional Government, drinking water and sanitation services have become a mandatory matter for local governments. The framework for thinking about this theory is to see a society as a dynamic system consisting of various subsystems that are interconnected with one another. Structural-functional theory views that all of these sub-systems have consequences for the others as well as the system as a whole. This study aims to describe the effectiveness of the PAMSIMAS program in Nagari Padang Air Cold, Sangir Jujan District, South Solok Regency. The results of this study indicate that the implementation of the PAMSIMAS program in Nagari Padang Air Cold, Sangir Jjujan District, South Solok Regency, when viewed from the source approach in obtaining both physical and non-physical resources, it can be said to be quite effective, but when viewed from the it is still less effective because the process has not been able to run properly in accordance with the goals and objectives previously set from the PAMSIMAS program